Photoinactivation of Photosystem II at low light intensity. Mathematical models - Szilárd, András; Sass, László; Vass, Imre (Acta Biologica Szegediensis, 2002)
We studied the effect of low light intensity on Photosystem II (PSII) of thylakoid membranes isolated form spinach. The application of low frequency single turnover flashes results in the decreased oxygen evolving activity of PSII. This effect was explained in the framework of a model, which assumes that saturating visible light flashes at low frequency can result in the degradation of the D1 protein, since S23/Q8 and S2/Qa recombinations generate singlet oxygen through the intermediate triplet chlorophyll formation. We propose a pathway for the light-induced transitions and dark period processes of the S-states, which results the best fit of our experimental data.